2017
DOI: 10.1186/s12966-017-0594-8
|View full text |Cite
|
Sign up to set email alerts
|

Does replacing sedentary behaviour with light or moderate to vigorous physical activity modulate inflammatory status in adults?

Abstract: BackgroundSedentary behaviour, obesity and insulin resistance are associated with pro-inflammatory status. Limited data on whether physical activity modulates inflammatory status and counteracts obesity and insulin resistance associated low-grade inflammation exist. Our objective was to investigate associations between objectively measured physical activity and inflammatory status, and specifically whether substituting daily sedentary behaviour with light activity or moderate to vigorous physical activity (MVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 59 publications
8
41
0
Order By: Relevance
“…Lifestyle factors are associated with subclinical inflammation, and dietary habits may play a central role in the regulation of chronic inflammation, at least in non‐pregnant adults . Regular physical activity and replacement of sedentary behaviour with moderate to vigorous physical activity have been associated with more favourable inflammatory profiles in adults . On the other hand, adverse lifestyle habits such as smoking and alcohol consumption have been linked with elevated inflammatory status and more pro‐inflammatory diets, in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Lifestyle factors are associated with subclinical inflammation, and dietary habits may play a central role in the regulation of chronic inflammation, at least in non‐pregnant adults . Regular physical activity and replacement of sedentary behaviour with moderate to vigorous physical activity have been associated with more favourable inflammatory profiles in adults . On the other hand, adverse lifestyle habits such as smoking and alcohol consumption have been linked with elevated inflammatory status and more pro‐inflammatory diets, in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…We identified significant associations between more pro‐inflammatory paternal and PGM E‐DII scores and higher risk of childhood overweight/obesity, which may be partly explained by food modelling practices at home . The difference in E‐DII scores between mothers and fathers in our study is noteworthy and is keeping with previously reported gender differences in DII scores among adults . Further studies examining the human intergenerational influence of dietary inflammation on offspring outcomes are warranted.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, previous studies states that increasing amounts of sedentary behaviour were associated with unfavourable alterations in the inflammatory profile, which increases the inflammation. [23] When we compare moderate with high intensity exercise, we found a significant improvement in total antioxidant and leptin values with moderate intensity exercise in both athletes and non-athletes. Our findings are supported by the studies, which states that moderate intensity exercise inhibits free radical generation and increases the antioxidant levels [24] and inflammation, while high intensity exercise induces the free radical generation.…”
Section: Discussionmentioning
confidence: 80%